1996
DOI: 10.1021/jf9507147
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Phase of Heat-Denatured Lysozyme with Novel Antimicrobial Action

Abstract: The structure and antimicrobial function of hen egg white lysozyme was investigated by means of thermal denaturation at 80 °C (pH 7.2), which leads to irreversible denaturation. With an increase in the heating time (up to 30 min) of lysozyme, the soluble fraction showed progressive decrease in its enzyme activity that coincided with the formation of a slower migrating band on the acid PAGE. Fluorescence spectra revealed that, as the extent of denaturation increases, the surface hydrophobicity and the exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
2
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 32 publications
3
135
2
5
Order By: Relevance
“…Second, the bacteriostatic and bactericidal properties of lysozyme have been the subject of many studies, and over the last 10 years, several authors have proposed a novel antibacterial mechanism of action for lysozyme that is independent of its 1,4-␤-Nacetylmuramidase activity. These reports are based on unique bactericidal properties observed with partially or completely denatured lysozymes having reduced or no enzymatic activity against both gram-positive and gram-negative bacteria (2,10,13,16). For example, Ibrahim et al (10,13) demonstrated inactivation by heat-denatured lysozyme of an Escherichia coli K-12 strain, which was relatively insensitive to native lysozyme.…”
mentioning
confidence: 99%
“…Second, the bacteriostatic and bactericidal properties of lysozyme have been the subject of many studies, and over the last 10 years, several authors have proposed a novel antibacterial mechanism of action for lysozyme that is independent of its 1,4-␤-Nacetylmuramidase activity. These reports are based on unique bactericidal properties observed with partially or completely denatured lysozymes having reduced or no enzymatic activity against both gram-positive and gram-negative bacteria (2,10,13,16). For example, Ibrahim et al (10,13) demonstrated inactivation by heat-denatured lysozyme of an Escherichia coli K-12 strain, which was relatively insensitive to native lysozyme.…”
mentioning
confidence: 99%
“…This catalytic activity can damage bacterial cell walls, but it is only effective against gram positive bacteria. However, several researches showed enhancement of this catalytic activity of lysozyme by heating or irradiation can reduce the survival rate of gram negative bacteria as well as gram positive bacteria (Ibrahim et al, 1996;Schmidt et al, 2007). Therefore, SDE may contribute benefits beyond provision of nutrients.…”
Section: Lysozyme In Spray-dried Eggmentioning
confidence: 99%
“…the main proteins in hen egg white and it has an ability to cause lysis of bacterial cells [65]. Lysozyme is a globular protein that has a net charge of +9 at neutral pH, and was initially used for the formation of DNA gel particles [52].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%